Outcomes of hemodynamic support with Impella in very high-risk patients undergoing balloon aortic valvuloplasty: Results from the Global cVAD Registry. (1st August 2017) - Singh, Vikas; Yadav, Pradeep K.; Eng, Marvin H.; Macedo, Francisco Yuri; Silva, Guilherme V.; Mendirichaga, Rodrigo; Badiye, Amit P.; Sakhuja, Rahul; Elmariah, Sammy; Inglessis, Ignacio; Alfonso, Carlos E.; Schreiber, Theodore L.; et al.
Abstract: Background: Reports on the role of hemodynamic support devices in patients with severe aortic stenosis (AS) and left ventricular (LV) dysfunction undergoing balloon aortic valvuloplasty (BAV) are limited. Methods: Patients were identified from the cVAD registry, an ongoing multicenter voluntary registry at selected sites in North America that have used Impella in > 10 patients. Results: A total of 116 patients with AS who underwent BAV with Impella support were identified. Mean age was 80.41 ± 9.03 years and most patients were male. Mean STS score was 18.77% ± 18.32, LVEF was 27.14% ± 16.07, and 42% underwent concomitant PCI. In most cases Impella was placed electively prior to BAV, whereas 26.7% were placed as an emergency. The two groups had similar baseline characteristics except for higher prevalence of CAD and lower LVEF in the elective group, and higher STS score in the emergency group. Elective strategy was associated higher 1-year survival compared to emergency placement (56% vs. 29.2%, p = 0.003). One-year survival was higher when BAV was used as a bridge to definitive therapy as opposed to palliative treatment (90% vs. 28%, p < 0.001). On multivariate analysis, STS score and aim of BAV (bridge to definitive therapy vs. palliative indication) were independent predictors of mortality. Conclusion: In this large cohort of patients with AS and severe LV dysfunction undergoing BAV, our results demonstrates feasibility and promising long-term outcomes using elective Impella support with the intention to bridge to a definitive therapy.